The Idea of Motion in Modernist Painting - Žvirblytė, Milda (Religija ir kultūra, 2011)
This article deals with the problem of the phenomenological discourse as an methodological issue raised in the modernist Lithuanian painting of the second half of the twentieth century aiming to reveal the idea of motion in painting. In this case the abstract pictures by Kazimiera Zimblytė and Eugenijus Antanas Cukermanas, created in the eighth−tenth decades, have been chosen to discuss. Both artists are interested in abstract plastic idea – how to create the impression of a motion of a spot, plane, background on the canvas surface. The question is: how to explain the idea of motion in a painting, who does constitutes movement, what makes count as an object in motion, what produces a perception of movement in painting? Article approaches the idea of motion on the basis of painting with the reference to the theory of perception by phenomenologist Maurice Merleau-Ponty according to the following concepts: the relationship between figure and background, the visual field, the Chiasm.